BENANG MERAH PERJANJIAN: ANALISIS TEKS PERJANJIAN DAN PENGGENAPANNYA DI DALAM YESUS - Sabda Budiman; Robi Panggara (Institut Agama Kristen Negeri Kupang, 2022)
The Bible contains two great themes that are very dizziness, namely the Old Testament (OT) and the New Testament (NT). The concepts of these two agreements are very different. Therefore, many church schools arose because of these two concepts of the covenant. But basically these two agreements are not contradictory and contradictory. The two support each other and complement each other. Thus, the problem to be answered in this study is how the relationship between these two agreements and what is the basis of the relationship. The purpose of this study is to explain the relationship between the OT and the NT of the predetermined parts of the Bible. The methods used in this study are exegesis approaches and qualitative methods. As for the results of this study is all the covenants that God made with the patriarchs only as a picture of the main character, Namely Jesus Christ. All the themes discussed, the author wants to reveal that the common thread of the Bible and the main character discussed is Jesus Christ. God is faithful to His promises.